Behavioral teratogenicity induced by maternal food restriction: maternal cannibalism and poor reflex development in offspring - Esther Lopes Ricci; Maria Martha Bernardi; Silvana Lima Górniak; Helenice Souza Spinosa (Biotemas)
http://dx.doi.org/10.5007/2175-7925.2014v27n2p185